2022
DOI: 10.3390/nu14071443
|View full text |Cite
|
Sign up to set email alerts
|

A High-Protein and Low-Glycemic Formula Diet Improves Blood Pressure and Other Hemodynamic Parameters in High-Risk Individuals

Abstract: Low-caloric formula diets can improve hemodynamic parameters of patients with type 2 diabetes. We, therefore, hypothesized that persons with overweight or obesity can benefit from a high-protein, low-glycemic but moderate-caloric formula diet. This post-hoc analysis of the Almased Concept against Overweight and Obesity and Related Health Risk- (ACOORH) trial investigated the impact of a lifestyle intervention combined with a formula diet (INT, n = 308) compared to a control group with lifestyle intervention al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
(56 reference statements)
1
10
0
Order By: Relevance
“…Our data confirmed that it was not the baseline leptin concentration, but an early and distinct leptin lowering [33,34] within the first month of intensive meal replacement that was predictive for long-term weight loss and this is in line with other dietary intervention studies demonstrating lower leptin levels in subjects without weight regain [35]. By using the meal replacement, not only effects on leptin and weight, but also an improvement in blood pressure could be observed [19], which could be explained by the fact that leptin mediates the relationship between fat mass and blood pressure [22]. In a previous work, we showed that the reduction of fasting insulin played an important role in weight reduction [18] and in combination with leptin we could demonstrate that those people with the strongest leptin reduction and tendencial higher insulin reduction had lost weight most effectively.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our data confirmed that it was not the baseline leptin concentration, but an early and distinct leptin lowering [33,34] within the first month of intensive meal replacement that was predictive for long-term weight loss and this is in line with other dietary intervention studies demonstrating lower leptin levels in subjects without weight regain [35]. By using the meal replacement, not only effects on leptin and weight, but also an improvement in blood pressure could be observed [19], which could be explained by the fact that leptin mediates the relationship between fat mass and blood pressure [22]. In a previous work, we showed that the reduction of fasting insulin played an important role in weight reduction [18] and in combination with leptin we could demonstrate that those people with the strongest leptin reduction and tendencial higher insulin reduction had lost weight most effectively.…”
Section: Discussionsupporting
confidence: 90%
“…The ACOORH study is an international, multicentre randomised-controlled trial analysing the effect of a meal-replacement based lifestyle intervention in overweight or obese persons with components of the metabolic syndrome. Details had been published before [15][16][17][18][19]. In brief, individuals aged 21-65 years, with a body mass index (BMI) of 27-35 kg/m 2 and/or a waist circumference of ≥88 (females) or ≥102 cm (males) and fulfilling at least one of the following criteria of the metabolic syndrome: (a) fasting blood glucose (FBG) 100-125 mg/dL, (b) triglycerides 150-400 mg/dL, (c) high-density lipoprotein (HDL)-cholesterol < 40 mg/dL, or (d) untreated systolic blood pressure of 140-160 mmHg or diastolic blood pressure of 90-100 mmHg or anti-hypertensive medication were eligible for participation.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…When the physical activities of people are limited, their dietary assessment will be an important issue to control weight. Moreover, a diet rich in fruits, vegetables, low-fat dairy products, fiber and minerals, would produce a potent antihypertensive effect [3,4]. Many studies show that there is a positive relationship between being overweight or obese and blood pressure (BP) with the risk of hypertension [5,6].…”
Section: Introductionmentioning
confidence: 99%